The relationship between Board Characteristics, Corporate Governance Score (CG Score) and Accounting Conservatism of Listed Companies in the Market for Alternative Investment (MAI) - Khunkaew, Rojana; Wichianrak, Jittima; Suttipun, Muttanachai; Boonthip, Kallaya; Chukaeo, Thanaphon; Musik, Tanyarak; Musidang, Witchayaporn (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
This study aims to investigate the relationship among Board characteristics, CG Score and Accounting Conservatism by collecting data from the annual report of 320 listed companies in the Market for Alternative Investment (MAI) during the period of 2016 – 2019. In this study indicators of Board Characteristics are size of committee, Board independent, finance and accounting knowledge, dual position, foreigner committee and committee gender. For CG Score, the study uses CG score from the annual report. Additionally, in the main variable accounting caution, this study employs executive judgment in the calculation of Modified Jones Model to measure the Accounting Conservatism. The results demonstrate there is no significant association between Board Characteristics and Accounting Conservatism. In contrast, the findings reveal a positive association between CG Score and Accounting Conservatism. The results are benefit to the business and that can apply the principles of good corporate governance to increase the efficiency of Accounting Conservatism, moreover, the findings are useful for stakeholders to make decision.